Mensuração do balanceamento de linha no setor de corte de aves de uma empresa frigorífica do Paraná - Trassi, Janaina (2023)
Line balancing is a production strategy that seeks to improve productivity and process efficiency by optimizing the workflow. Thus, this case study aimed to analyze the line balancing in the cutting sector of a poultry slaughterhouse located in the city of Campo Mourão/Paraná. For the development of the work, a survey of the process activities was carried out, the determination of times considered standard for carrying out the activities, the analysis of the number of employees, as well as the desired production rate and the available time of production of the slaughterhouse. Balancing was measured in the two Shawarma cone lines in the first shift, which had to be adjusted to the type of production process, taking into account the speed of the cone and the number of employees at each workstation, as these factors are efficiency indicators of the line in the fridge. It is concluded, with the measurement of the cone lines of the Shawarma in use, some idleness, with an average efficiency of 110%. Thus, some adjustments are recommended regarding the number of employees, changing from 40 to 38, and the cone speed, changing from 76 cones/minute to 68 cones/minute, through a new proposed scenario, taking into account the rate of desired production, within the established time of work by the company, remaining at 100% average efficiency.